(untitled) (Perner’s Contacts, 2023)
This review paper deals with operation and maintenance of railway vehicles in the context of technical specifications for interoperability (TSIs). The attention is paid especially to the new process of vehicle authorization and extension of the maintenance system based on entity in charge of maintenance (ECM) on the locomotives and passenger coaches – generally the news in this branch introduced by the so-called technical pillar of the 4th Railway Package.